Life at school : an ethnographic study - Thapan, Meenakshi (New Delhi ; Oxford : Oxford University Press, 2006)
This volume explores the complex relationship between ideas, institutions and the people in them, by examining the case of the Rishi Valley School, which is informed by the world-view of the renowned philosopher Jiddu Krishnamurti.
Previous ed.: 1991.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Krishnamurti, J. -- 1895-1986.; Rishi Valley School (India); Educational anthropology -- India -- Andhra Pradesh; Teacher-student relationships -- India -- Andhra Pradesh; High schools -- India -- Andhra Pradesh -- Sociological aspects